Exploring the Use of Authentic Materials for Reading Activity at A Vocational School - Alam, Nur; Kalukar, Ventje Janny; Hermagustiana, Istanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
This research explores teacher strategies in adapting authentic materials for reading instruction at vocational schools, identifying challenges faced by teachers and students. The study aims to investigate these strategies and challenges among tenth-grade AKL students at SMK Sangatta Utara during the 2023/2024 academic year. This qualitative case study examines the use of authentic materials in reading instruction at a vocational school. Data were collected through observations, semi-structured interviews, and field notes with one English teacher and six tenth-grade students. Techniques included purposive sampling and Creswell’s (2014) data analysis method for organizing, coding, and interpreting findings. The study found that teachers employed strategies for selecting and adapting authentic materials for reading instruction, such as advertisements and articles, that were relevant to students' interests. Challenges included limited internet access, insufficient learning media, and students' difficulties with vocabulary and engagement. Teachers mitigated these challenges through personal hotspots, group activities, and additional support. This study reveals effective strategies for using authentic materials in teaching reading, highlighting the benefits of relevance and collaboration. However, challenges like limited internet access and multimedia resources persist. Recommendations include improving technological infrastructure, providing teacher training, and fostering local collaborations to enhance the use of authentic materials and support student engagement and learning outcome